The Effect of Information Sharing on the Assessment of Supply Chain Performance in Uncertain Conditions - Daryosh Mohamadi Janaki; Hamidreza Izadbakhsh; Seyed Morteza Hatefi (International Journal of Information and Communication Technology Research, 2018)
The role of information sharing in achieving competitiveness has been recently a topic of considerable interest among researchers at various levels, including company, business, and supply chain management. Information technology has a significant effect on improving supply chain performance either directly or indirectly. In this paper, the impact of information sharing on competitive strategies and supply chain proceedes of the petroleum products distribution company is investigated in some provinces (Chaharmahal and Bakhtiari, Kohgiluyeh and BoyerAhmad, Tehran, Isfahan) in the conditions of uncertainty using z-number, Dubois and Prade methods. Here, the amount of confidence in human knowledge such as logistic, business, strategic, tactical etc., is included in the calculations. Fuzzy Theory in use to consider the existing epistindc uncertainty in the expert opinion the about the information sharing and supply chain performance indicators. According to the results of this research it can be concluded that the information unity has a direct and significant communication with competitive supply chain strategies, and supply chain competitive strategies in turn, have a direct and significant relationship with supply chain performance.